First record of the nesting whitefly, Paraleyrodes minei, in Greece - Kalaitzaki, A. P.; Tsagkarakis, A. E.; Ilias, A. (ENTOMOLOGIA HELLENICA, 2016)
On late June 2015, the nesting whitefly Paraleyrodes minei Ιaccarino (Hemiptera: Aleyrodidae) was recorded for first time in Greece. Its occurrence was observed on leaves of sweet orange [Citrus sinensis (L.) Osbeck] trees at Platanias, Chania, on the underside of which tiny white “nests” were observed, due to the woolly waxy material secreted by females, around themselves, as well as by the filamentous translucent wax rods extending from the dorsum of late nymphal instars. In our surveys P. minei was observed at low or moderate population densities. Information on its morphology, biology and present geographical distribution is provided.